Eagle days : a Marine legal/infantry officer in Vietnam - Griffis, Don W. (Donald Warner), 1942- (Book collections on Project MUSE., 2007)
Much has been written about America's war in Vietnam, and an enduring and troubling subtext is the composition of the body of soldiers that made up the US troop deployment. This is the author's personal record of experiencing what the military should do best, and what it becomes when esprit de corps, discipline, and a sense of purpose decay.